The Position of the Qanun Jinayat as a Forum for the Implementation of Sharia in Aceh in the Indonesian Constitution - Din, Mohd; Abubakar, Al Yasa' (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2021)
The purpose of this paper is to describe the position of the Qanun Jinayat as a forum for the implementation of Sharia in Aceh within the framework of the Indonesian constitution. It is considered essential because the implementation of Sharia is conducted based on the UUPA (Law on Governing of Aceh). However, its implementation is often misunderstood, causing the implementation of Sharia to face many challenges from various parties, including the government's official institutions. This article is written to answer the main problem: the alignment of regulations, qanuns, with other laws and regulations. This study is normative legal research using a legal history approach. The analytical tools used are the theory of leveling norms and asymmetric decentralization. The study results show that the Sharia qanuns in Aceh, especially the Qanun Jinayat, have a different position from the regional regulations in other provinces in Indonesia. The difference lies in the special right of the Government of Aceh as a region with asymmetrical decentralization to make its regulations which at a certain level are permitted to be inconsistent with the laws on higher hierarchy. However, it must still align with the basic norms as the primary reference. The existence of special rights for Aceh is considered natural because of its long history, mainly when it is associated with the development of criminal law in Indonesia, which until now still uses the KUHP inherited from the Dutch East Indies. This specificity is a legal order regarding autonomous or special regions.